Research on the process of decomposing woody fibers for carbon cycle with different environmental factors. Issue 4 (July 2021) - Zhang, Xiaoduo; Liu, Wenhao; He, Shupeng
Abstract: The decomposition process of wood fiber is an important part of carbon cycle, and fungi play a crucial role in the decomposition process of wood fiber. Therefore, it is of great significance to analyze the effect of fungi on the decomposition process of wood fiber and explore the factors affecting the decomposition process. Based on the useful attributes found in the data set, first, the paper put forward the log linear regression model, and draw the relationship curve of wood fiber decomposition rate with temperature and mycelium growth rate. At the same time, the reliability and significance of the model are analyzed, and the model is tested. Next, in order to combine the interactions between different fungal species, based on the influence data of humidity tolerance and growth rate on decomposition rate given in the topic, the paper establish a multiple linear regression model to explore the influence of environmental factors and the interaction between populations on decomposition rate.